Bancroftian filarial pleural effusion. Issue 817 (November 1993) - Aggarwal, J.; Kapila, K.; Gaur, A.; Wali, J. P.
Abstract : This paper describes a case of filarial pleural effusion, the fifth such to be reported. Microfilariae of Wuchereria bancrofti were detected in the pleural fluid on cytological examination. There was a prompt and complete response to treatment with diethylcarbamazine. There were, however, no symptoms and signs of tropical pulmonary eosinophilia nor any peripheral eosinophilia.